Is Sharing Economy Contributing to Sustainable Development? - Laktiš, Peter; Mihaľová, Paulína (Studia Ecologiae et Bioethicae, 2025)
This paper deals with the concept of the sharing economy, which has been extended to a lot of different areas, increasing its influence on our lives in recent years. New forms of business models have enabled greater demand by providing easier access to the use of products and services, and at the same time opened the potential to higher supply and created possibility to share unused assets to more providers. The term “sharing economy” covers a broad universe of products and services encompassing different motives for sharing. The presented paper divides sharing economy platforms based on their contribution towards environmental sustainability. This distinction between different forms of sharing economy platforms is important as sustainable aspect of the sharing economy is often advertised. The existing research conducted in this field is insufficient and calls for further attention.